Energy and amino acid neurotransmitter metabolism in astrocytes - Waagepetersen, Helle (Henry Stewart Talks, 2013)
Basic elements of brain glutamate metabolism and homeostasis, The glutamate-glutamine cycle, anaplerosis and de-novo synthesis of glutamine, Glutamate oxidation including pyruvate recycling including investigative methodologies, Brain energy metabolism and lactate as a potential alternative energy substrate, The role of glycogen in brain function and metabolism